Bacillus subtilis Expressing the Infectious Pancreatic Necrosis Virus VP2 Protein Retains Its Immunostimulatory Properties and Induces a Specific Antibody Response - Félix Docando; Félix Docando; Noelia Nuñez-Ortiz; Gabriela Gonçalves; Gabriela Gonçalves; Cláudia R. Serra; Cláudia R. Serra; Eduardo Gomez-Casado; Diana Martín; Beatriz Abós; Aires Oliva-Teles; Aires Oliva-Teles; et al. (Frontiers in Immunology, 2022)
Bacillus subtilis has been documented in the past years as an effective probiotic for different aquacultured species, with recognized beneficial effects on water quality, fish growth and immune status. Furthermore, its potential as a vaccine adjuvant has also been explored in different species. In the current work, we have used B. subtilis spores as delivery vehicles for the presentation of the VP2 protein from infectious pancreatic necrosis virus (IPNV). For this, the VP2 gene was amplified and translationally fused to the crust protein CotY. The successful expression of VP2 on the spores was confirmed by Western blot. We then compared the immunostimulatory potential of this VP2-expressing strain (CRS208) to that of the original B. subtilis strain (168) on rainbow trout (Oncorhynchus mykiss) leukocytes obtained from spleen, head kidney and the peritoneal cavity. Our results demonstrated that both strains significantly increased the percentage of IgM+ B cells and the number of IgM-secreting cells in all leukocyte cultures. Both strains also induced the transcription of a wide range of immune genes in these cultures, with small differences between them. Importantly, specific anti-IPNV antibodies were detected in fish intraperitoneally or orally vaccinated with the CRS208 strain. Altogether, our results demonstrate B. subtilis spores expressing foreign viral proteins retain their immunomodulatory potential while inducing a significant antibody response, thus constituting a promising vaccination strategy.